1984
DOI: 10.1111/j.1476-5381.1984.tb10120.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effect of methylxanthines on acetylcholine release from electrically‐stimulated brain slices

Abstract: On the other hand the mechanism through which methylxanthines decrease ACh release remains obscure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Although caffeine is a benzodiazepine receptor antagonist, this property is only present at toxic levels of plasma caffeine (File et al, 1982) and cannot explain the effects observed in the present study. Recent research suggests that antagonism of adenosine A(2a) receptors (Pedata et al, 1984;Varani et al, 2000;Scammell et al, 2001) or an increase in sympathetic activation/catecholamines (Kamimori et al, 2000) may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Although caffeine is a benzodiazepine receptor antagonist, this property is only present at toxic levels of plasma caffeine (File et al, 1982) and cannot explain the effects observed in the present study. Recent research suggests that antagonism of adenosine A(2a) receptors (Pedata et al, 1984;Varani et al, 2000;Scammell et al, 2001) or an increase in sympathetic activation/catecholamines (Kamimori et al, 2000) may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects appear to involve purine receptors (Pedata et al, 1984). It is therefore difficult to account for their disappearance, the unchanged effect of adenosine and the increase in the A1 receptor high affinity subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine, added to the superfusing solution at the concentration of 50 piM enhances acetylcholine (ACh) release. Conversely, at a concentration of 0.5 mM caffeine decreases ACh release (Pedata et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Opposite effects from A 1 -mediated synaptic inhibition are elicited by A 2A receptor activation, which has been shown to mediate excitatory actions in synaptic function [ 62 64 ]. In the hippocampus in vitro, A 2A receptor stimulation results in a Ca 2+ -dependent release of acetylcholine [ 65 , 66 ].…”
Section: Role Of Adenosine In Cerebral Transmission Under Normoxic Comentioning
confidence: 99%